Iron preparations for women of reproductive age with iron deficiency anaemia in pregnancy (FRIDA): a systematic review and network meta-analysis. Issue 7 (July 2021) - Rogozińska, Ewelina; Daru, Jahnavi; Nicolaides, Marios; Amezcua-Prieto, Carmen; Robinson, Susan; Wang, Rui; Godolphin, Peter J; Saborido, Carlos Martín; Zamora, Javier; Khan, Khalid S; Thangaratinam, Shakila
Summary: Background: Numerous iron preparations are available for the treatment of iron deficiency anaemia in pregnancy. We aimed to provide a summary of the effectiveness and safety of iron preparations used in this setting. Methods: We did a systematic review and network meta-analysis of randomised trials. We searched MEDLINE, Embase, Cochrane Central Register of Controlled Trials, trial registers, and grey literature for trials published in any language from Jan 1, 2011, to Feb 28, 2021. We included trials including pregnant women with iron deficiency anaemia and evaluating iron preparations, irrespective of administration route, with at least 60 mg of elemental iron, in comparison with another iron or non-iron preparation. Three authors independently selected studies, extracted data, and did a risk of bias assessment using the Cochrane tool (version 1.0). The primary outcome was the effectiveness of iron preparations, evaluated by changes in haemoglobin concentration at 4 weeks from baseline. The secondary outcomes were change in serum ferritin concentration at 4 weeks from baseline and treatment-related severe and non-severe adverse events. We did random-effects pairwise and network meta-analyses. Side-effects were reported descriptively for each trial. This study is registered with PROSPERO, CRD42018100822. Findings: Among 3037 records screened, 128 full-text articles were further assessed for eligibility. Of the 53 eligible trials (reporting on 9145 women), 30 (15 interventions; 3243 women) contributed data to the network meta-analysis for haemoglobin and 15 (nine interventions; 1396 women) for serum ferritin. The risk of bias varied across the trials contributing to network meta-analysis, with 22 of 30 trials in the network meta-analysis for haemoglobin judged to have a high or medium global risk of bias. Compared with oral ferrous sulfate, intravenous iron sucrose improved both haemoglobin (mean difference 7·17 g/L, 95% CI 2·62–11·73; seven trials) and serum ferritin (mean difference 49·66 μg/L, 13·63–85·69; four trials), and intravenous ferric carboxymaltose improved haemoglobin (mean difference 8·52 g/L, 0·51–16·53; one trial). The evidence for other interventions compared with ferrous sulfate was insufficient. The most common side-effects with oral iron preparations were gastrointestinal effects (nausea, vomiting, and altered bowel movements). Side-effects were less common with parenteral iron preparations, although these included local pain, skin irratation, and, on rare occasions, allergic reactions. Interpretation: Iron preparations for treatment of iron deficiency anaemia in pregnancy vary in effectiveness, with good evidence of benefit for intravenous iron sucrose and some evidence for intravenous ferric carboxymaltose. Clinicians and policy makers should consider the effectiveness of individual preparations before administration, to ensure effective treatment. Funding: None.